(untitled) (The Planet, 2023)
Introduction:Anemia was first linked to CKD over 170 years ago by Richard Bright. As kidney disease progresses, anemia increases in prevalence, affecting nearly all patients with stage 5 CKD. Anemia in CKD is associated with reduced quality of life and increased cardiovascular disease, hospitalizations, cognitive impairment, and mortality. This study aimed to analyzethe extent of anemia with progressing stages of CKD. Methods and Materials: This cross-sectional study was conducted in the Department of Nephrology, Dhaka National Medical College Hospital,for 1 year; from January 2020 to January 2021. A total of 50 subjects were included in this study as per inclusion criteria.Result: Among the study subjects, most of the patients 44% suffered from severe anemia followed by 36% patients who had moderate anemia.According to extent of CKD, most of the patients 50% had stage 5 CKD (ESRD), followed by 20% patients who had stage 3 CKD, and the rest 20% patients suffered from stage 4 kidney disease. Among the patients who had stage 3 kidney disease, 16% patients had mild anemia, followed by 8% patients who had moderate anemia, and the rest 6% patients had severe anemia. Conclusion:In this study, among the patients who had the end-stage renal disease (ESRD) or stage 5 CKD, 14.0% of patients had moderate anemia and 36.0% of patients had severe anemia.So, this study concluded that the extent of anemia increases with progressing stages of CKD.